Pitfalls in dengue case management - Siripen Kalayanarooj; Mukda Vangveeravong (Open Journal of Tropical Medicine - Peertechz Publications, 2021)
Dengue is one of the most common mosquito-borne viral diseases affecting both children and adults worldwide, particularly in the countries of Asia and Latin America [1]. An estimated 100-400 million infections occur annually with 50,000 deaths per year [1]. Most symptomatic patients with dengue present with mild non-specific symptoms that do not require hospitalization [1-3]. Patients with mild to moderate dengue severity often have clinical manifestations of poor appetite, nausea, vomiting, abdominal pain, and dehydration [2,3]. A number of patients with mild to moderate dengue severity need supportive and symptomatic treatment in the hospital, which mainly comprises intravenous fluid therapy [1-4]. Severe or complicated cases require hospitalization according to the disease because of plasma leakage [Dengue Hemorrhagic Fever (DHF)/Dengue Shock Syndrome (DSS)] and bleeding [1-4].